Leadership Strategies for the Success of Foreign-Owned U.S. Startups (International Journal of Scientific Research and Management (IJSRM), 2025)
The rise of digital commerce has enabled foreign entrepreneurs to launch and scale eCommerce businesses beyond their home markets. However, entering a foreign market presents significant challenges, including regulatory complexities, cultural differences, logistical constraints, intense competition, and consumer trust-building. The ability of foreign-owned eCommerce startups to successfully navigate these challenges is largely influenced by transformational leadership, a leadership style that fosters vision, innovation, adaptability, and team empowerment. This research explores the role of transformational leadership in overcoming market entry barriers and driving the sustainable success of foreign-owned eCommerce ventures. Using a mixed-methods approach, this study examines the impact of transformational leadership on foreign entrepreneurs through a combination of case studies, industry reports, and survey-based insights from eCommerce startup founders and executives. The findings identify key leadership traits essential for success in foreign markets, including strategic foresight, cultural intelligence, resilience, and the ability to drive digital transformation. Furthermore, this study highlights how transformational leaders leverage technology-driven business models, customer-centric marketing strategies, and adaptive decision-making frameworks to establish competitive advantages in new markets. Additionally, this research uncovers effective leadership strategies that foreign-owned eCommerce startups can adopt to mitigate risks and accelerate growth. These include building trust through localized branding, establishing strategic partnerships with local stakeholders, utilizing data-driven decision-making, and fostering a collaborative and agile company culture. By integrating transformational leadership principles with digital business strategies, foreign entrepreneurs can enhance their ability to scale their businesses while navigating the complexities of global eCommerce ecosystems.